Recycling of iron-containing deposits - the main way to increase the efficiency of water-protective measures on the territory of the Tom lower course; MATEC Web of Conferences; Vol. 85 : Chemistry and Chemical Technology in XXI Century (CCT 2016) - Popov V. K. Viktor Konstantinovich (2016, 2016)
Title screen